(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article analyzes the current state of housing and communal services, as threatening the development of the national economy. Identify destructive effects on the environment due to the impact of housing and communal services. Indicated complex infrastructure maintenance Housing. Detailing the main and auxiliary functions of housing and communal services. It turns out the role of outsourcing, as outsourcing and other organizations optimize performance and reduce costs enterprise-based concentration on core areas, or secondary transmission or non-core functions outsourced. Fundamental developments systematized considerable number of scientists on the role of outsourcing in energy efficiency strategy Housing. Outlined aspects of the National Reform Program Housing for 2015–2025 years.